Development and Optimization of a Fluorescent Imaging System to Detect Amyloid-β Proteins: Phantom Study. (13th June 2018) - Tes, David; Kratkiewicz, Karl; Aber, Ahmed; Horton, Luke; Zafar, Mohsin; Arafat, Nour; Fatima, Afreen; Avanaki, Mohammad RN
Alzheimer disease is the most common form of dementia, affecting more than 5 million people in the United States. During the progression of Alzheimer disease, a particular protein begins to accumulate in the brain and also in extensions of the brain, ie, the retina. This protein, amyloid-β (Aβ), exhibits fluorescent properties. The purpose of this research article is to explore the implications of designing a fluorescent imaging system able to detect Aβ proteins in the retina. We designed and implemented a fluorescent imaging system with a range of applications that can be reconfigured on a fluorophore to fluorophore basis and tested its feasibility and capabilities using Cy5 and CRANAD-2 imaging probes. The results indicate a promising potential for the imaging system to be used to study the Aβ biomarker. A performance evaluation involving ex vivo and in vivo experiments is planned for future study.